Enniatin B and beauvericin are common in Danish cereals and show high hepatotoxicity on a high‐content imaging platform. Issue 5 (15th September 2016) - Svingen, Terje; Lund Hansen, Niels; Taxvig, Camilla; Vinggaard, Anne Marie; Jensen, Udo; Have Rasmussen, Peter
ABSTRACT: Mycotoxins are fungi‐born metabolites that can contaminate foods through mould‐infected crops. They are a significant food/feed‐safety issue across the globe and represent a substantial financial burden for the world economy. Moreover, with a changing climate and fungal biota, there is now much discussion about emerging mycotoxins that are measurable at significant levels in crops world‐wide. Unfortunately, we still know very little about the bioavailability and toxic potentials of many of these less characterized mycotoxins, including the large family of enniatins. In this study, we present new occurrence data for enniatin A, A1, B, B1 and beauvericin in four Danish crops: oat, wheat, and barley from the 2010 harvest, and rye from 2011 harvest. The occurrence of the four enniatins were B > B1 > A1 > A. Enniatin B was detected in 100% of tested samples regardless of crop type. In addition to occurrence data, we report a proof‐of‐concept study using a human‐relevant high‐content hepatotoxicity, or "quadroprobe, " assay to screen mycotoxins for their cytotoxic potential. The assay was sensitive for most cytotoxic compounds in the 0.009–100 µM range. Among eight tested mycotoxins (enniatin B, beauvericin, altenariol, deoxynivalenol, aflatoxin B1, andrastin A, citrinin, and penicillic acid), enniatin B and beauvericin showed significant cytotoxicity at a concentration lower than that for aflatoxin B1, which is the archetypal acute hepatotoxic and liver‐carcinogenic mycotoxin. Hence, the quadroprobe hepatotoxicity assay may become a valuable assessment tool for toxicity assessment of mycotoxins in the future. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1658–1664, 2017.